Population Pharmacokinetics of Temocillin Administered by Continuous Infusion in Patients with Septic Shock Associated with Intra-Abdominal Infection and Ascitic Fluid Effusion - Perrin Ngougni Pokem; Xavier Wittebole; Christine Collienne; Hector Rodriguez-Villalobos; Paul M. Tulkens; Laure Elens; Françoise Van Bambeke; Pierre-François Laterre (MDPI AG, 2022)
Temocillin is active against Gram-negative bacteria, including many extended-spectrum β-lactamase (ESBL)-producing Enterobacterales. We studied its pharmacokinetics in plasma and ascitic fluid after intravenous administration of a loading dose of 2 g over 30 min, followed by continuous infusion of 6 g/24 h, to 19 critically-ill patients with septic shock associated with complicated intra-abdominal infection. We established a pharmacokinetic model describing unbound temocillin concentrations in plasma and ascitic fluid and performed Monte-Carlo simulations to evaluate the probability of target attainment (PTA) of unbound concentrations (100% fT > MIC, i.e., unbound concentrations remaining above the MIC during 100% of the time) for the applied and hypothetical dosing regimens. The temocillin AUC in ascitic fluid was 46% of the plasma AUC. Plasma unbound concentrations were best described by a two-compartment model, and an additional compartment was added to describe unbound concentration in ascitic fluid, with renal clearance as a covariate. Dosing simulations showed that 90% PTA was achieved in the plasma with the current dosing regimen for MIC ≤ 16 mg/L (EUCAST susceptibility breakpoint) but not in the ascitic fluid if renal clearance was ≥40 mL/min. Hypothetical dosing with a higher (a) loading dose or (b) infused dose allowed to reach target concentrations in ascitic fluid (a) more rapidly or (b) sustainably, but these simulations need to be evaluated in the clinics for safety and efficacy.